Evidence for insulin-induced internalization and degradation of insulin receptors in rat adipocytes. - Green, A (1982)
We have investigated the theory that the insulin-induced loss of insulin binding from adipocytes is due to internalization of insulin receptors. Cell-surface receptors were assessed by the binding capacity of intact cells at 16 degrees C. Total (i.e., cell-surface plus intracellular) receptors were assessed by solubilizing the cells in 1% Triton X-100 and then measuring binding by the solubilized extract. Intracellular receptors were measured by treating the cells with trypsin before solubilizing them. The trypsin treatment removed greater than 90% of the cell-surface binding, so that any significant binding by soluble extracts of these cells must represent intracellular receptors. Adipocytes were incubated with insulin (100 ng/ml) with or without chloroquine (0.2 mM) for 4 hr. Insulin alone resulted in a 62% loss of cell-surface receptors, but only a 46% loss of total receptors, and a 170% increase in intracellular receptors, suggesting that the lost cell-surface receptors were internalized, where some were degraded. Insulin in the presence of chloroquine resulted in a 34% loss of cell-surface receptors, but no loss of total receptors, and a 300% increase in intracellular receptors. Thus, in the presence of chloroquine receptors were internalized but not degraded. The loss of cell-surface receptors and appearance of intracellular receptors were time and dose dependent and were linearly related. These results demonstrate that insulin causes translocation of insulin receptors from the cell surface to the cell interior, where they can be degraded (or inactivated) by a chloroquine-sensitive process.